Roles of forkhead box O (FoxO) transcription factors in neurodegenerative diseases: A panoramic view. (October 2019) - Hu, Wei; Yang, Zhi; Yang, Wenwen; Han, Mengzhen; Xu, Baoping; Yu, Zihao; Shen, Mingzhi; Yang, Yang
Highlights: The basic knowledge regarding NDDs and FoxO family, and the characterization and regulation of FoxOs in CNS were introduced. We discussed the diverse roles of FoxOs in the pathogenesis and development of NDDs, including AD, PD, ALS, and HD. Several promising pharmacotherapy treatments targeting FoxOs network were summarized. This review provided a comprehensive summary of FoxOs in the development and treatment of NDDs. Abstract: Neurodegenerative diseases (NDDs), which are among the most important aging-related diseases, are typically characterized by neuronal damage and a progressive impairment in neurological function during aging. Few effective therapeutic targets for NDDs have been revealed; thus, an understanding of the pathogenesis of NDDs is important. Forkhead box O (FoxO) transcription factors have been implicated in the mechanisms regulating aging and longevity. The functions of FoxOs are regulated by diverse post-translational modifications (e.g., phosphorylation, acetylation, ubiquitination, methylation and glycosylation). FoxOs exert both detrimental and protective effects on NDDs. Therefore, an understanding of the precise function of FoxOs in NDDs will be helpful for developing appropriate treatment strategies. In this review, we first introduce the post-translational modifications of FoxOs. Next, the regulation of FoxO expression and post-translational modifications in the central nervous system (CNS) is described. Afterwards, we analyze and address the important roles of FoxOs in NDDs. Finally, novel potential directions of future FoxO research in NDDs are discussed. This review recapitulates essential facts and questions about the promise of FoxOs in treating NDDs, and it will likely be important for the design of further basic studies and to realize the potential for FoxOs as therapeutic targets in NDDs.